Exploring psychosocial factors influencing sexually transmitted infection intention testing among medical students: a cross-sectional study in two universities - Loaiza-Guevara, Valentina; Acosta, María Alejandra Gómez; Álvarez, Angie Valeria Aguirre; Martínez, Valentina Agudelo; Montoya, María Camila Montes; Ramírez, Alexandra Agudelo; Izquierdo-Condoy, Juan S. (Frontiers in Public Health, 2024)
Background Despite the significant global burden of sexually transmitted infections (STI), detection rates are poor. Acceptance of these tests is influenced by several factors that have not been explored among Colombian medical students. Objectives The aim of this study was to describe the behaviors and psychosocial factors toward STI screening among medical students of two universities in Pereira, Colombia, between March and June 2020. Methods An observational, cross-sectional study was conducted with 284 medical students in the first 3 years of undergraduate at two universities. An online, self-administered survey was conducted between March 2020 and June 2020, using an instrument from the “STI Testing Questionnaire,” to assess behaviors and psychosocial factors toward STI testing. Frequencies and percentages were used for descriptive analysis. The association between characteristics and psychosocial factors with STI testing intention was obtained using a logistic regression model. A p-value <0.05 was accepted as statistically significant for all analyses. Results A total of 284 medical students participated in this study. The majority were female (56.7%), and 53.2% were from private universities. Eighty-four point 5% (84.5%) had risky sexual behaviors, and only 32.4% reported intentions to be tested for STIs. Among the psychosocial factors, 64.1% reported high social pressure, and 43.0% reported social fear. An association with the intention to undergo STI testing was identified in those who had been previously tested (OR = 2.486; 95% CI: 1.492–4.142) and in those who engaged in risky sexual behaviors (OR = 3.537; 95% CI: 1.437–8.704). Conclusion Medical students exhibit a high prevalence of risky sexual behaviors but show a disturbing lack of intention to undergo STI screening. Prior experiences significantly influence screening intentions, while social pressure and fear also play a role. These insights can serve as a basis for targeted interventions to improve STI screening rates and enhance sexual health education among Colombian medical students.